Functional state and protein-synthesizing function of the liver of laying hens under conditions of cadmium loading : ст. - Kraikivska, H. Yu.; Gutyj, B. V. et.al.; Hunchak, V. M.; Martyshuk, T. V.; Khariv, I. I.; Slobodiuk, N. M.; Demus, N. V.; Vus, U. M. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2023)
The toxicity of cadmium in the bird's body depends on the penetration method, the total dose, and the duration of poisoning. That is why the work aimed to study the effect of Cadmium on liver function disorders. To achieve the set goal in experiments on chickens under cadmium load, it was necessary to solve the following tasks: to study the effect of cadmium on the protein synthesis function of the liver of laying hens; to study the effect of cadmium on the functional state of the liver of laying hens. 24 laying hens aged 78 weeks were selected for research. These chickens were divided into three groups: control and two experimental, taking into account their age and weight. Chickens from the control group received compound feed and clean water without adding cadmium sulfate. In the chickens of the experimental groups, cadmium sulfate was added to the drinking water in different concentrations for 30 days: the first group (R1) – 2 mg per kilogram of body weight, the second group (R2) – 4 mg per kilogram of body weight. According to the conducted studies, it was found that in laying hens under conditions of cadmium load, the functional state of the liver is disturbed, as evidenced by the increased activity of aminotransferases in their blood serum. It is worth noting that the highest activity of alanine and aspartate aminotransferases was in the blood serum of laying hens of the second experimental group on the 21st day of the experiment. The results indicate an increase in destructive processes in the body of laying hens due to cadmium loading. In laying hens under cadmium load, the liver's protein synthesis function is suppressed, manifested by a decrease in the level of total protein and albumins, with a simultaneous increase in the level of globulins. Drinking cadmium sulfate with water in a larger dose (4 mg/kg of body weight) was accompanied by a more probable decrease in total protein and albumin level than drinking cadmium sulfate in a smaller dose (2 mg/kg of body weight). Under cadmium load, an albumin-globulin disproportion occurs, which is indicated by the value of the A/G ratio. In the chickens of the first experimental group, it was found that the value of the A/G ratio on the 21st day of the experiment was 0.42, while in the second experimental group, it was lower and was 0.39, respectively, against the control 0.52.
Keywords: heavy metals; cadmium; poultry; aminotransferases; важкі метали; кури-несучки; кадмій